Cecal volvulus in a rare intestinal malformation. - Kamaid, Emil; Croci, Fabio; Rabellino, Joaquín (Cirugía del Uruguay, 1987)
A case o! reversed bowel rotation is presented. A exceptional situation of anomalous intestinal rotation and fixation, that ocurred in an old woman, complicated with volvulus o! the right colon. Sorne embyologic, anatomic, pathologic, clinic and therapeutic considerations about this disease are done.